Relevance versus connection: Discourse and text as units of analysis - Garrido, Joaquín (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The interpretation of speech can be dealt with in terms of grammar, if grammatical categories are extended beyond the sentence. After briefly reviewing speech acts, discourse acts and relevance, two units are thus posited, the discourse and the text, and they are defined in strictly linguistic-theoretical terms, by means of a principle of connection. Following this principle, sentences are linked using additional information, which is not explicitly represented in the sentence. The resulting units are structured sequences of sentences, called discourses, which are, in turn, linked in a structured way into larger units, called texts.